Ausencia de figura paterna y su incidencia en el consumo de sustancia psicotrópica en un adolescente de 19 años de edad del Centro de Rehabilitación CETAD paz del cantón el Empalme - Palma Palma, Gloria Liliana (2021)
The present case study was developed on how the absence of a father affects the childhood of a 19-year-old adolescent and how this leads his life to the consumption of psychotropic substances in a cetad of the Empalme canton. Which presented an alteration of the sensoperception, affecting his quality of life, and his family nucleus. Taking into account that parental affection influences a very important role in the social and cognitive development of a child so that it has a good growth and development. In collecting information, techniques such as semi-structured interview, direct observation, the beck test, and the htp test were used in order to reach a diagnosis, as well as cognitive behavioral therapy techniques, through these Automatic thoughts could be detected by doing cognitive restructuring and in this way providing guidelines to the patient for their daily improvement.